2016
DOI: 10.1016/j.jsat.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Executive Function in Patients With Substance Use Disorder: A Comparison of Inventory- and Performance-Based Assessment

Abstract: The BRIEF-A inventory was the most sensitive measure of executive function in patients with substance use disorder, followed by measures of cold executive function. BRIEF-A should therefore be considered as an integral part of the clinical routine when assessing patients with SUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 70 publications
3
78
0
8
Order By: Relevance
“…The finding that self-reported, but not performance-based, changes in executive abilities were observed in this study is consistent with other research suggesting self-report measures may be more sensitive to differences in executive deficits among adolescent drug users [19] substance dependent populations [36,37] and other clinical populations [35]. Growing evidence suggests performance-based and self-report measures of executive functioning may be tapping into different constructs as the two approaches do not often yield significant correlations and those correlations are often small.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that self-reported, but not performance-based, changes in executive abilities were observed in this study is consistent with other research suggesting self-report measures may be more sensitive to differences in executive deficits among adolescent drug users [19] substance dependent populations [36,37] and other clinical populations [35]. Growing evidence suggests performance-based and self-report measures of executive functioning may be tapping into different constructs as the two approaches do not often yield significant correlations and those correlations are often small.…”
Section: Discussionsupporting
confidence: 92%
“…Executive function is complex construct as its neuropsychological study and assessment involve multiple distinct yet interrelated abilities and neuroanatomical substrates [2,4]. Previous studies have often examined a restricted range of executive abilities [22,23,31] or focused on a particular measurement approach (performance base versus self-report measures) [12,18], though the two approaches may be assessing different constructs [35] and possess differential sensitivity to deficits [19,36,37]. The current study assessed executive abilities using multiple formats and across a broad range of executive abilities.…”
Section: Journal Of Addiction Research and Therapymentioning
confidence: 99%
“…Validity characteristics were confirmed according to different methods, content and face validity were evaluated at the first step of the research as scale preparation, and factor analysis method was used to confirm factors of the scale in the Persian version. Different studies have validated the BRIEF-A inventory in different target populations, including patients suffering from binge eating disorder (19,27), patients with substance use disorder (20), neuropsychiatric patients (21), and schizophrenia (22), and have suggested that the BRIEF-A inventory is an appropriate tool in measuring different aspects of executive function, including emotional impairments and social functioning (20). Further studies have confirmed that BRIEF-A is sensitive to mild cognitive impairment (28).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have introduced BRIEF as the most sensitive measure of executive function, each on a different target populations, including obese patients suffering from binge eating disorder (19), patients with substance use disorder (20), neuropsychiatric patients (21), and schizophrenia (22). However, studies evaluating BRIEF-A have declared complexity in assessment of executive function and have suggested that feasibility of BRIEF-A has to be evaluated for different cultures and target populations (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation